2021
DOI: 10.3390/jcm10102198
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of 0.66% Povidone-Iodine Eye Drops on Ocular Surface Flora before Cataract Surgery: A Nationwide Microbiological Study

Abstract: A multicenter, nonrandomized, prospective, controlled study was conducted to evaluate, as perioperative prophylactic treatment, the anti-infective effectiveness of 0.66% povidone-iodine eye drops (IODIM®) against the bacterial flora of the conjunctival surface of patients who undergo cataract surgery. Eye drops containing 0.66% povidone-iodine were applied to the eye undergoing cataract surgery; the untreated contralateral eye was used as control. One hundred and twenty patients set to receive unilateral catar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Several formulations were used as preoperative prophylaxis prior to cataract surgery. In 2021 Musumeci et al demonstrated that 0.6% PVI eye drop (IODIM, Medivis, Catania, Italy) used for 3 days in patients who underwent cataract surgery were effective in reducing the conjunctival bacterial load [35]. Accordingly, Pinna et al showed that 0.6% PVI eye drop had rapid in vitro antimicrobial activity against common etiologic agents of ocular infection, such as S. epidermidis, S. aureus, and P. aeruginosa [36].…”
Section: Antiseptics and Disinfectantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several formulations were used as preoperative prophylaxis prior to cataract surgery. In 2021 Musumeci et al demonstrated that 0.6% PVI eye drop (IODIM, Medivis, Catania, Italy) used for 3 days in patients who underwent cataract surgery were effective in reducing the conjunctival bacterial load [35]. Accordingly, Pinna et al showed that 0.6% PVI eye drop had rapid in vitro antimicrobial activity against common etiologic agents of ocular infection, such as S. epidermidis, S. aureus, and P. aeruginosa [36].…”
Section: Antiseptics and Disinfectantsmentioning
confidence: 99%
“…From this perspective, the evaluation of risk-benefit ratio led us to consider that the use of antibiotics in place of PVI can be considered not justified. Since the safety and effectiveness of PVI has been well acknowledged by several scientific studies [1,35], ocular surgeons can use PVI without the risk of incurring medical claims for not having administered antibiotics.…”
Section: Risk Management Strategiesmentioning
confidence: 99%
“…In order to avoid the adverse event, there are some registered preventive actions for endophthalmitis, such as the use of 0.66% povidone-iodine eye drops before surgery [28] . Or use of intracameral antibiotics during surgical procedures [29,21] can be considered as a preventive approach to infections.…”
Section: Discussionmentioning
confidence: 99%
“…26 Here, our results also supported that 0.5% PVP-I was already beneficial for POE prophylaxis for effectively reducing the risk of POE, which was consistent with the conclusion in Rosario’s study. 27 It seems that a low concentration PVP-I might realize financial savings as well as improved antisepsis at the same time, which is worth promoting. However, further large-scale randomized controlled trials were needed to evaluate the optimum concentration of PVP-I.…”
Section: Discussionmentioning
confidence: 99%